Transfer of Funds Via Brilink an Analytical Study of Transactions Within the Framework of Wakalah Bil Ujrah Contract - Setiawan, Muhammad Nanda; Hana, Kharis Fadlullah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
With today's economic developments, Brilink has emerged as an initiative to provide more efficient and flexible services to the community. Brilink represents a collaboration between Bank BRI and its customers. Within its system, once a partnership is established and officially incorporated into a single corporation, it facilitates ease of transactions both within the same bank and across different banks. This service benefits customers and other parties wishing to conduct transactions without the cumbersome process of visiting a bank directly. This paper aims to elaborate on fund transfers via Brilink and analyze transactions in the context of the wakalah bil ujrah contract. Using a qualitative descriptive method, the study’s findings indicate that fund transfer transactions through Brilink do not constitute riba or usury from an Islamic perspective. This is primarily because the contract is based on mutual consent, involves no coercion, and is mutually beneficial. It also ensures transparency, wherein the customer pays a fee to the agent for the transactional services provided. This payment represents voluntary assistance or a form of mutual aid